New technologies to plan and mediate reading: Helpful, pleasant and indispensable - Netzel, Rosangela Maria de Almeida; Oliveira, Marilu Martens (Revista Hipótese, 2022)
Aiming to facilitate teaching planning and practice based on new technologies, this action research culminated in the creation and the implementation of a product (PLANPED), based on conceptions of Lévy (1999), Ferreira and Duarte (2012) and Demo (2009) on educational computing; Liberato and Fulgencio (2007) and Martins (1994) about reading; and Cosson (2007), about literature. Thus it contributed with the qualitative research in education, focusing the literary mediation in initial education.
Keywords: Reading; Planning; Technology; Formation